PolarGap: Recovery Lake Airborne Radar Data - Matsuoka, Kenichi; Diez, Anja (Norwegian Polar Institute, 2019)
Airborne radar data collected during the PolarGap project funded by the European Space Agency. The radar system PASIN of the British Antarctic Survey was used for data collection.